Socio-economic and Gender Disparities in PsychologicalDistress and Marital Adjustment Among Spouses ofHepatitis C Patients: A Quantitative Assessment (Journal of Asian Development Studies, 2024)
The present study examines differences in psychological distress and marital adjustment betweenspouses of Hepatitis C patients based on socioeconomic and gender status, specifically addressingdissimilarities in emotional and couple functioning due to economic and gender disparities.Hepatitis C is a chronic and progressive disease, and there is a substantial caregiver burdenrequired, which should increase stress and negatively impact marital quality. With the datacollected from 200 spouses of Ayub Medical Complex and Combined Military HospitalAbbottabad Pakistan, this research investigates the moderating effects of economic resources andgender roles on psychological distress and other factors pertinent to marital satisfaction, such asaffection expressing marital adjustment and dyadic cohesion. Results identified by the study showthat compared to spouses with higher SES, participants with lower SES have significantly elevatedlevels of psychological distress and reduced marital adjustment, indicating the role of economicstress in caregiver stress. The female spouses continue to display higher levels of distress andlower marital satisfaction and cohesiveness than male spouses, replicating the usual femalegender role expectations of the traditional caregiver. Also, gender and economic level crosstabulations show differences in coping and support seeking and, hence, mental health andrelationship quality. These results indicate the further imperative of targeting specificpsychological and social support for economically disadvantaged and female carers to alleviatetheir specific known burdens, providing a foundation for developing policies dealing with maritalstress in chronic illness situations, among other proposals